MAIN ASPECTS OF INTEGRATION OF EXPERT EXPERTISE INTO THE LEGAL SPACE FOR STATE DECISION-MAKING - Zaiets, Oleksandr (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of the article is to study the main aspects of the systematization of theoretical approaches and the analysis of practical mechanisms for integrating professional expertise into the legal space in order to increase the efficiency, validity and transparency of state decision-making. Special attention is paid to identifying problems of national regulation and formulating proposals for improving legislation in this area. Methods: the study is based on both general scientific methods and specific legal methods of comparative analysis (comparative science), with the help of which various scientific provisions and doctrinal approaches are developed to understand the concept and essence of professional expertise, as well as their significance in the analyzed legal area. The following scientific methods were used in the research process: analytical method - for studying regulatory legal acts of Ukraine and international experience; comparative legal method - for comparing models of expert support in different legal systems; systemic approach - for analyzing the relationships between the expert environment and state administration institutions; synthesis and generalization - for formulating conclusions and practical recommendations. Results: as a result of the research: the key principles of legal integration of expert knowledge into public administration (constitutional principles of the rule of law, legal certainty, impartiality and proportionality, as well as basing the effective integration of independent expertise on the principles of independence of experts; professional competence; procedural guarantees; legal certainty and connection with the principle of good governance) were identified; foreign experience in involving expertise in the formation of public policy was analyzed; the main problems of Ukrainian legislation were identified, including the fragmentation of regulation, the absence of a single regulatory act, the lack of quality standards for expert activity; conceptual ways of improving the legal mechanism for involving expert expertise were proposed, including the need to develop a special law, create an open register of experts and digitalize procedures. Discussion: the article considers key aspects of integrating expert expertise into the legal space, aimed at ensuring the validity, objectivity and effectiveness of state decisions. Special attention is paid to the regulatory and legal mechanisms of interaction between the expert environment and state institutions, the role of the interdisciplinary approach and the principles of transparency. The need to form a systemic model for involving experts in public administration is substantiated.